Digitial Marketing Strategy of Property Agents in Civil Departement - Masrizal; Muhammad Giatman; Yuliana (Institute of Computer Science (IOCS), 2022)
This study aims to determine how the digital marketing strategy of property agent in the civil department at SMKN 1 Sumatera Barat. This study uses a descriptive approach. The research instrument in the form of a questionnaire filled out by students was then analyzed to see the proportion of student interest and the form of entrepreneurship they have on social media platforms. Digital marketing strategy for real estate agents in civil department i.e. Social media, Email Marketing, Digital Pay per Click Advertising, Search Engine Optimization.